GENERATION FEATURES OF CYCLE OPERATIONS FOR PRODUCTION MACHINE VARIABLE-FREQUENCY DRIVE IN LOW-VELOCITY ZONE OF ACTUATOR - Nikolay F. Karnaukhov; Maxim N. Filimonov; Andrey I. Izyumov (Advanced Engineering Research, 2012)
The step change of the autonomous voltage inverter carrier frequency is proposed for operating enhancement of the frequency-controlled electric drive of the production machines in the «retarted and creeping» motion speed area. The introduction of the double-triple carrier frequency «submodulation» allows providing the induction motor stator current with nonsinusoidality ratio at least 4,3 % which aids the steady motion of the actuator and accuracy increase of its stop block in the positioning zone.